-18m-24=-6+48

Simple and best practice solution for -18m-24=-6+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18m-24=-6+48 equation:


-18m-24=-6+48

We simplify the equation to the form, which is simple to understand
-18m-24=-6+48

We move all terms containing m to the left and all other terms to the right.
-18m=-6+48+24

We simplify left and right side of the equation.
-18m=+66

We divide both sides of the equation by -18 to get m.
m=-3.6666666666667

See similar equations:

| 11-3x=-4x | | 7x+3=4x+3 | | 4d+9=7d | | 5b+7-12b-29= | | 4n+1=5n+20 | | 14n-6-5n-29= | | 3[x-4]=8[x-9] | | 10x+3x+8x= | | 5times=135 | | (x-1)(x^2+5x-6)= | | (6x+6)+(10x-30)= | | 2x^2-6x=80 | | 7-(4n-8)=7-5n | | 5[x-4]=2[x-7] | | 9x+4+3+8=12 | | 7x^2+76x=8 | | 18c-4-2c+12= | | 54=x+5x | | 8u-6u=6 | | 5[x-3]=4[x+2] | | 11=4+v | | 12p+6=8p+30 | | 9x-30=2x+5 | | 47+11x=-30 | | (4x+3)=25 | | 179=6-u | | X-5.67=8.2 | | 12+x=3(3-2x) | | 47+11x=30 | | x(2x+1)=5x+1 | | 4[2-x]=5[x-2] | | -6u=4 |

Equations solver categories